Improving quality in healthcare to makes a satisfied patient ; mini review - Faris Mana AIi AL Mahri, ABDAN MOHAMMED ALMNSOUR , YAHYAA SAEID HAMD AL MUTAYF, MUHAMAD SALIH ALI AL RAMLAN, GHALIB HUSSEIN ALI AL-SALIM, HAMAD MASTOOR HAMADI AL ALHARETH, NADER ALI DAFER AL ALHARETH, HAMAD MAHDI MUHAMMAD AL-YAMI, HUSSAIN MESFER BIN DHAFER ALALHARETH, HEBATALLAH ABDULLAH J ALMAKRAMI (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Efforts to improve the quality, safety, and efficiency of health care provision have often focused on changing approaches to the way services are organized and delivered. Continuous quality improvement (CQI), an approach used extensively in industrial and manufacturing sectors, has been used in the health sector. Despite the attention given to CQI, uncertainties remain as to its effectiveness given the complex and diverse nature of health systems. This review assesses the effectiveness of CQI across different health care settings, investigating the importance of different components of the approach